Interleukin-10 as a potential biomarker reflecting the multidimensional pathological network in patients with severe fever with thrombocytopenia syndrome: viral load, cytokine storm, organ damage, and immune suppression - Zhang, Ruihua; Wang, Jingxia; Xu, Yanli; Ma, Ruize; Peng, Wan; Jiang, Zhouling; Wu, Hongxiao; Zhao, Chenxi; Lin, Ling; Zhang, Mengyuan; Chen, Zhihai; Duan, Jianping; et al. (Frontiers in Immunology, 2026)
BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is a highly fatal infectious disease, potentially driven by cytokine storms. This study evaluates plasma interleukin-10 (IL-10) as a prognostic biomarker by analyzing its association with disease severity and outcomes, aiming to improve early risk stratification and clinical management.MethodsA retrospective study was conducted on SFTS admitted to Yantai Infectious Disease Hospital from 2022 to 2024. Patients were grouped into survivors (n=160) and non-survivors (n=55). Clinical data from the first 24 hours of admission were collected. To determine independent risk factors influencing prognosis, logistic regression analysis was utilized, particularly assessing the clinical predictive significance of IL-10.ResultsThis investigation assessed 215 SFTS patients, where 160 were placed in the survival category and 55 in the mortality category. Multivariate analysis identified IL-10 as an independent predictor of mortality in individuals with SFTS. Receiver Operating Characteristic curve analysis indicated that IL-10 possessed a strong predictive capability for patient mortality, achieving an area under the curve (AUC) of 0.8044 (95% CI: 0.7388 - 0.8701; P < 0.0001). The optimal cutoff was 29.1 pg/ml (sensitivity 74%, specificity 78%). Furthermore, correlation analysis indicated significant associations between IL-10 and various clinical parameters (all P < 0.05), which included SFTS virus RNA, inflammatory markers (such as hypersensitive C-reactive protein and Procalcitonin), signs of multi-organ dysfunction (including Creatine kinase, Lactate dehydrogenase, Aspartate aminotransferase, Blood urea nitrogen, and Creatinine), coagulation irregularities (such as decreased Platelets, prolonged Activated partial thromboplastin time, and elevated D-dimer levels), and indicators of immune suppression (including reduced CD3+, CD4+, and CD8+ T cell counts). Furthermore, IL-10 were found to positively correlate with various pro-inflammatory cytokines including Interleukin-6, Tumor Necrosis Factor-alpha, and Interferon-γ. Patients with IL-10 ≥29.1 pg/ml had higher intensive care unit admission (P<0.0001), SFTS-associated encephalopathy (P = 0.0178), lower viral clearance (P<0.0001) within the first 14 days following symptom onset, and reduced 28-day survival (P = 0.0007). Continuous monitoring of IL-10 showed declining levels in survivors but rising levels in non-survivors.ConclusionPlasma IL-10 is an early prognostic biomarker for SFTS, with serial monitoring guiding clinical decisions to improve outcomes.